MODEL OF ISLAMIC EDUCATION AT THE MADRASAH DINIYAH ULYA - Supriyono Supriyono (TAWASUT, 2023)
Abstract Islamic education is a planned effort in preparing people to recognize, understand, appreciate, and believe in the teachings of Islam accompanied by demands to respect other religions in inter-religious relations to create national unity and integrity. Madrasah Diniyah Ulya is a non-formal Islamic religious education unit that provides Islamic religious education as a complement for high school/vocational/MA/equivalent students or children of the same educational age who have not attended formal education. This level is taken in 2 (two) years with a minimum study time of 18 students a week with a duration of 45 minutes per lesson hour. The purpose of Madrasah Diniyah Ulya is to develop, expand and deepen the Islamic religious education obtained for students to develop their lives, fostering students to have experience, knowledge, worship skills, commendable traits, attitudes and behaviors that are useful for personal development, fostering students to have the ability to carry out their life duties in society and to be devoted to Allah SWT in order to achieve happiness in the world and the hereafter, and prepare students for can attend Islamic religious education at higher educational institutions. Islamic Education Materials at Madrasah Diniyah Ulya consist of moral formation which is carried out with knowledge (understanding), charity (habituation) and exemplary (uswatun hasanah). The books that are often used as references or handbooks in madrasah diniyah, are almost entirely in Arabic or Arabic books combined with regional languages, such as Javanese (kitab beard).The Ulya Madrasah Diniyah Education Model can be developed from several components including: institutions, management, teachers and education staff, students, funding, infrastructure, curriculum, learning, learning evaluation, and supervision, monitoring, evaluation and reporting as well as maintaining the existence of madrasah diniyah. Key Words: Model, Islamic Education and Madrasah Diniyah Ulya